2021
DOI: 10.1088/2515-7647/abf942
|View full text |Cite
|
Sign up to set email alerts
|

A physical origin of cross-polarization and higher-order modes in two-dimensional (2D) grating couplers and the related device performance limitations

Abstract: We explore scattering effects as the physical origin of cross-polarization and higher-order modes in silicon photonic 2D grating couplers (GCs). A simplified analytical model is used to illustrate that in-plane scattering always takes place, independent of grating geometry and design coupling angle. Experimental investigations show furthermore that grating design parameters are especially related to the modal composition of both the target- and the cross-polarization. Scattering effects and the associated cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We have shown that in general 2D GCs convert a part of the power of a given input polarization into its orthogonal counterpart -an effect, which we assign as a linear cross-polarization [22]. We have further indicated in-plane scattering as the physical origin of this conversion [23] -an issue, which inevitably occurs due to the finite size of the diffracting elements of 2D GCs with respect to the optical waveguide mode. In our most recent work [24], the impact of the cross-polarization has been investigated on system level.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have shown that in general 2D GCs convert a part of the power of a given input polarization into its orthogonal counterpart -an effect, which we assign as a linear cross-polarization [22]. We have further indicated in-plane scattering as the physical origin of this conversion [23] -an issue, which inevitably occurs due to the finite size of the diffracting elements of 2D GCs with respect to the optical waveguide mode. In our most recent work [24], the impact of the cross-polarization has been investigated on system level.…”
Section: Introductionmentioning
confidence: 83%
“…Previous analyses state that polarization-related issues can be attributed to a scattering in the grating's plane. The latter is particularly strong, when an array of elements with identical scattering properties is given [23]. This is the case of uniform 2D GCs.…”
Section: B Segmented 2d Grating Couplersmentioning
confidence: 99%
“…The related polarization crosstalk was observed in experiments [4] and it was shown that it is associated with a loss of polarization orthogonality [5]. To address the issue of cross-polarization, its physical background was investigated [6]. We indicated in-plane scattering at the grating perturbing elements as the limiting process behind cross-polarization.…”
Section: D Grating Couplers For Improved Polarization Handlingmentioning
confidence: 99%
“…While we found 24) that the cross-polarization scales with the grating's perturbation strength (thus, limiting the coupling efficiency), we indicated in-plane scattering as its physical origin. 25) The latter is caused by the finite size of the grating perturbing elements with respect to the incident optical field. The presence of in-plane scattering and thus of cross-polarization is the main reason for PDL in 2D-GRCs.…”
Section: Optimization Of Two-dimensional Grating Couplers In 025 μM P...mentioning
confidence: 99%